Effects of Processing Methods on Proximate Composition of Decorticated Castor Seeds (Ricinus Communis L.) (Global Journal of Science Frontier Research, 2020)
Nutritive values in raw, autoclaved, boiled, fermented, soaked, and toasted castor oil seeds (Ricinus communis L.), Zibo Castor No. 3 variety, collected from Ado-Ekiti metropolis, Nigeria were evaluated. The treatments consisted of six processing methods and three levels. Samples exhibited significant differences (p˂0.05) compared to the control sample and among one another in terms of all the parameters examined. There was a reduction in crude protein (CP), moisture, lipids, and ash contents with an increase in all the treatment methods adopted. However, moisture and ash increased, irregularly along the periods of autoclave treatment. There was an increase in Crude fiber (CF) and nitrogen-free extract (NFE) with the increase in autoclaving, boiling, fermenting, soaking, and toasting. Cases of irregular decrease and increase of values were, however observed along with the trend of periods of each treatment. Owing to its quality of parameters examined, particularly protein, CF, ash, and NFE, castor seed sample boiled for 40 minutes (BCSC 40 ) was considered the best level among others. It was therefore recommended for fish feed formulation.
Keywords: castor seed; ricinus communis; autoclaving; boiling; fermenting; soaking; and toasting